KAJIAN PARTISIPASI PEREMPUAN PADA PEREKONOMIAN KELUARGA DI KAMPUNG PELANGI RANDUSARI - Marya Tisnandya; Landung Esariti; Mada Sophianingrum (Jurnal Planologi, 2021)
ABSTRACTThe objective of this study is to analyze the forms and the most influential factors of women's participation in the family economy of Kampung Pelangi Randusari. Women's participation activities are conducted via the provision of skills training and increased involvement in the formation of home based enterprises. By using quantitative methods, this article applied scoring and weighting analysis tool. Data collection was conducted by delivering questionnaires and interviews with 30 respondents of married couples. The results of this study indicate that the largest participation of women in the family economy is in the form of participation in labour, money, and individual asset. In addition, the most influential factor is the ability to optimally elaborate skills derived from training activities and the ability to manage home based enterprises in order to improve family welfare. Keywords: participation form, women participation, family economy  ABSTRAKPenelitian ini bertujuan untuk menganalisis bentuk dan faktor yang mempengaruhi partisipasi perempuan pada perekonomian keluarga di Kampung Pelangi Randusari. Kegiatan partisipasi perempuan dilakukan melalui pengadaan pelatihan keterampilan dan peningkatan keterlibatan pada pembentukan usaha mikro atau UMKM. Dengan menggunakan metode kuantitatif melalui alat analisis skoring dan pembobotan, pengumpulan data dilakukan melalui kuesioner dan wawancara terhadap 30 responden pasangan suami istri. Hasil dari penelitian ini menunjukkan bahwa partisipasi perempuan pada ekonomi keluarga paling besar dilakukan dalam bentuk partisipasi tenaga, uang, dan harta benda.Sedangkan faktor yang paling berpengaruh adalah faktor kemampuan untuk memanfaatkan hasil pelatihan dan mengelola usaha mikro yang bertujuan untuk meningkatkan kesejahteraan keluarga.  Kata Kunci: bentuk partisipasi, ekonomi keluarga, partisipasi perempuan